Detection of large deletion in human BRCA1 gene in human breast carcinoma MCF-7 cells by using DNA-Silver Nanoclusters. (14th December 2017) - Borghei, Yasaman-Sadat; Hosseini, Morteza; Ganjali, Mohammad Reza
Abstract: Here we describe a label-free detection strategy for large deletion mutation in breast cancer (BC) related gene BRCA 1 based on a DNA-silver nanocluster (NC) fluorescence upon recognition-induced hybridization. The specific hybridization of DNA templated silver NCs fluorescent probe to target DNAs can act as effective templates for enhancement of AgNCs fluorescence, which can be used to distinguish the deletion of BRCA 1 due to different fluorescence intensities. Under the optimal conditions, the fluorescence intensity of the DNA-AgNCs at emission peaks around 440 nm (upon excitation at 350 nm) increased with the increasing deletion type within a dynamic range from 1.0 × 10 −10 to 2.4 × 10 −6 M with a detection limit (LOD) of 6.4 × 10 −11 M. In this sensing system, the normal type shows no significant fluorescence; on the other hand, the deletion type emits higher fluorescence than normal type. Using this nanobiosensor, we successfully determined mutation using the non-amplified genomic DNAs that were isolated from the BC cell line.